Thermal bonding of thermoplastic microfluidic devices - Nor Aza Hussain (2014)
The field of microfluidics has become one of the most dynamic field in recent years. It has potential benefits of reduced size, improved performance, disposability, low cost, and reduced power consumption. Polymer materials like PMMA – (Poly (Methyl Methacrylate)), has become one of the most promising materials for microfluidics devices due to the advantages of low cost, ease of fabrication, biocompatibility and higher flexibility over glass and silicon. PMMA substrates are made commonly via micro-injection molding. There are various ways of bonding the PMMA substrate with a cover plate of the same material. In this project, thermal bonding was studied. Thermal bonding provides one of the easiest methods to bond 2 surfaces together. The effect of oxygen plasma surface treatment was also investigated and contact angles measurements were carried out to characterize the surfaces fabricated before bonding.